The influence of work values of college students on entrepreneurial intention: The moderating role of psychological capital - Tian, Lijun (Frontiers in Education, 2022)
Abstract: Purpose: The aim of this study is to determine the influences of work values on entrepreneurial intention among college students. The moderating role of psychological capital was also examined. Methods: A total of 723 college students were investigated with work values questionnaire, entrepreneurial intention scale and positive psychological capital Questionnaire. Results: Work values was significantly and positively correlated with entrepreneurial intention(r=0.23, P<0.001); Psychological capital was significantly and positively correlated with entrepreneurial intention(r=0.33, P<0.001); Psychological capital did not moderate the relationship between work values and entrepreneurial intention (ß=0.02, P>0.05); Hope moderated the relationship between work values and unconditional entrepreneurial intention(ß=0.09, P<0.05). The relationship between work values and unconditional entrepreneurial intention was stronger in the high hope group (simple slope=0.21, p<0.001) than in the low hope group (simple slope=0.07, p<0.001). Conclusion: Hope moderates the relationship between work values and unconditional entrepreneurial intention. Improving the quality of hope can be used as an intervention to improve college students' unconditional entrepreneurial intention.